2004
DOI: 10.1093/jn/134.4.940
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sodium Gluconate Protects Rats from Large Bowel Cancer by Stimulating Butyrate Production

Abstract: Butyrate has an antitumorigenic effect on colorectal cancer cell lines. Dietary sodium gluconate (GNA) promotes butyrate production in the large intestine. Accordingly, we examined the effect of dietary GNA on tumorigenesis in the large intestine in rats. Male Fisher-344 rats (n = 32) were divided into 4 groups: 2 diets (with or without 50 g GNA/kg basal diet) x 2 treatments (with or without carcinogen administration). Colonic tumors were induced by 3 intraperitoneal injections of azoxymethane (15 mg/kg body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 29 publications
1
25
0
2
Order By: Relevance
“…However, in the present study, we have shown that diet may play a role in minimizing colonization resistance as long as a specific preferred nutrient is not completely absorbed in the small intestine. That is, although it has been shown that the source of gluconate for E. coli colonization is the mouse intestinal tissue and not mouse chow (44), increasing the gluconate concentration in the intestine was possible since as much as 70% of the gluconate fed to animals reaches the cecum (20). Under these conditions, with 20 g/liter gluconate in the drinking water, small numbers of MG1655 bacteria were able to grow to high numbers in the presence of high numbers of …”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, we have shown that diet may play a role in minimizing colonization resistance as long as a specific preferred nutrient is not completely absorbed in the small intestine. That is, although it has been shown that the source of gluconate for E. coli colonization is the mouse intestinal tissue and not mouse chow (44), increasing the gluconate concentration in the intestine was possible since as much as 70% of the gluconate fed to animals reaches the cecum (20). Under these conditions, with 20 g/liter gluconate in the drinking water, small numbers of MG1655 bacteria were able to grow to high numbers in the presence of high numbers of …”
Section: Discussionmentioning
confidence: 99%
“…In rodent models, administration of both butyrateproducing bacteria and butyrate metabolic precursors has been shown to increase colonic levels of butyrate and decrease precancerous lesions correlating with increased splenic NK cells and decreased β-glucuronidase activities in fecal cultures, both of which associated with protection against CRC [67,101]. Butyrate also promotes apoptosis through the Wnt signaling pathway in CRC cell lines [102].…”
Section: Evidence For Correlations Of Microbiota With Crcmentioning
confidence: 99%
“…The basal diet of this experiment consisted of (g/kg) -cornstarch, 637; casein, 200; soybean oil, 50; cellulose powder (Oriental Yeast Co., Ltd., Yokohama, Japan), 50; mineral mixture, 50; vitamin mixture, 10; and DLmethionine, 3. Both the mineral and vitamin mixtures had an identical composition to that of Kameue et al 10) and were purchased from Oriental Yeast Co., Ltd. (Yokohama, Japan).…”
Section: )mentioning
confidence: 99%